Effects of post-bleeding vascular infusion of cattle with a solution of sugars, sodium chloride, and phosphates or with calcium chloride on carcass traits and meat palatability - Dobbels, T.E.; Hunt, Melvin C.; Schoenbeck, J.J.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We evaluated the effects of postexsanguination vascular infusion at 10% of live weight of a solution of sugars, sodium chloride, and phosphates (MPSC) or of calcium chloride on carcass traits and meat palatability. Dressing percentages were 4% higher for carcasses infused with the MPSC and 2.5 % higher for carcasses infused with calcium chloride than for controls. USDA quality grades were not affected by vascular infusion. Infusion with calcium chloride caused undesirable intermuscular fluid accumulation and two-toned color in several muscles. It also caused higher Warner- Bratzler shear values and lower trained sensory panel scores (P<.05). MPSC infusion may offer financial benefits by increasing dressing percent, but it has no other major effects.
Keywords: Beef; Vascular infusion; Meat quality; Meat palatability